Listening comprehension anxiety among monolingual and translingual practices in two public schools in Sabah, Malaysia - Majunggi, Jenniesy (2021)
Listening anxiety presents an imminent danger to foreign language acquisition. Anxiety prevents students from achieving excellent academic performance in learning a new language. Many studies have explored the methods to reduce learners’ listening anxiety, but only a few have investigated the relationship between foreign language anxiety (FLA) and listening proficiency in a multilingual context. Based on Vygotsky's SocialCultural Theory (1978) in language learning development, this research aims to determine the differences of students’ performance in listening comprehension through monolingual and translingual practices in a French foreign language classroom, to investigate the correlation of classroom language policy of both practices on language listening anxiety, and to analyze the practicality on the use of different language instruction facing language anxiety in the French language classroom. The present study utilized the mixed-method research data from students’ classroom assessment (CA) reports, the listening comprehension tests, classroom observations, and interviews of 56 French language learners in a secondary school in Sabah. The quantitative result indicated a significant increase in student performance and achievement in listening comprehension in a translingual classroom. Nonetheless, the data findings implied that translingual practices had no significant influence on students’ listening anxiety. The outcome of the interviews showed that students have positive opinions of translingual practices and believed that translingual practices increased their comprehension, efficacy, and motivation towards learning the French language. Three integral functions were involved in translingual practices: interpretive, managerial, and interactive, that facilitated students’ language acquisition. The result suggested that translingual practices reduced listening anxiety caused by language barriers in the classroom and resolved listening comprehension difficulties. This finding provides recommendations for new teaching and learning approaches for students, teachers, and policymakers as a stepping stone for further research in learning French as a foreign language studies in Malaysia.